Urban Housing Ownership: Factors Influenced The Problems Faced By The Bumiputera In The District Of Johor Bahru, Johor, Malaysia - Bujang, Ahmad Ariffian; Abu Zarin, Hasmah; Agus, Mohd. Razali (2008)
Bumiputera housing problems and issues in the urban areas begin from the process of urbanisation and industrialisation, which bring in many immigrants from rural areas. Most of these immigrants are bumiputera come from the lower and medium income groups. They can’t afford to pay rental or purchase houses at a higher price. Thus, it created socio-economic problems, especially in the urban areas. To solve these problems, the government intervention is needed. Government intervention can be in the form of introducing various housing policies and regulations. One of them is the introduction of Bumiputera Lot Quota Regulation. The aim of this regulation is to balance the distribution of property ownership, especially the residential units among the bumiputera and non bumiputera. Under this regulation, the developers had to allocate at least 30 percent from the total property development for the bumiputera’s quota, at discounted rate between 5 to 15 percent of the selling price. The State Authorities have the discretion to fix the discounted rate. Although this regulation was introduced for decades, under the New Economic Policy (NEP), 1971, the selling rate of these houses is still low, at an approximately 15 percent from the total allocated. Thus, it shows that property ownership among the bumiputera is still low. In Johor Bahru, the selling rate of these houses is approximately 15 percent of the allocated quota. A case study is carried out to identify the factors that influenced this problems and issues. In this case study, a field survey is carried out. The result from the analysis shows that, the factors which influenced the housing problems and issues among the bumiputera in Johor Bahru are, the offered selling price is high, difficult to secure end financing, difficult to allocate 10 percent deposit, type and accommodation of the house is unfavorable and the location is not strategic. However, the most important findings in this paper are, the regulations failed to achieve its goal and the affordable housing for most bumiputera is below RM150,000 per unit.